Energy revamping of solar panels through titania nanocomposite coatings; influence of aqueous silica precursor. Issue 37 (29th March 2016) - Smitha, V. S.; Vidya, K.; Jayasankar, M.; Peer Mohamed, A.; Hareesh, U. S.; Warrier, K. G. K.
Abstract : A novel, multifunctional, titania–silica–lanthanum phosphate (TSL) nanocomposite coating on solar panel modules was found to significantly increase the output voltage to ~15% under outdoor exposure leading to the energy revamping of solar panels. Abstract : An all-inorganic nanocomposite coating of titania has been found to revamp the reduction in efficiency of solar panels arising due to atmospheric pollution. A multifunctional, photoactive and hydrophobic titania–silica–lanthanum phosphate (TSL) nanocomposite having excellent anatase thermal stability is reported for the first time as alternative coatings on solar panel covers for maintaining the energy efficiency of panels over a period of time under outdoor conditions. The precursor source of silica has been found to significantly influence the photoactivity of titania in the nanocomposite under investigation. Polymeric silica is derived from the tetraethylorthosilicate precursor while particulate silica is aqueous colloidal silica. The enhanced photoactivity of the particulate titania–silica composition is attributed to the presence of phase pure anatase having an optimum crystallite size and surface area, achieved in the presence of silica. Lanthanum phosphate which has low water wettability is further influenced by particulate silica in providing better non-wetting behavior to the TSL nanocomposite. The presence of particulate silica in the TSL composite is superior to that containing polymeric silica in terms of crystallinity, photoactivity and low wettability. Thus, functional titania coatings possessing synergistic properties of the constituents can be designed from a less expensive and effective silica precursor. The all-inorganic system investigated in the present work is environmentally friendly and is stable over a wide range of temperatures. The feasibility of large-scale preparation and application of the particulate TSL nanocomposite coatings on solar panels under outdoor exposure has been demonstrated. The present novel approach for the development of aqueous-derived, self-cleaning, energy conserving coatings will lead to the energy revamping of solar panels and may have large-scale industrial applications.